Azerbaijan : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Azerbaijan during the 1990s. In 1992, approximately 70-80 percent of producer and consumer prices were liberalized, and enterprises were allowed greater latitude in their price and wage setting. However, price controls were applied on energy and bread prices, price markups remained controlled, and the price liberalization process was constrained by state procurement of major production items. Although the coverage of the state order system was gradually reduced, it still accounted for most of the production of 'strategic goods' at end-1994.